Sustainable Rail Transport Proceedings of RailNewcastle Talks 2016 (Lecture Notes in Mobility,, 2018)
This edited monograph presents the selected papers from RailNewcastle 2016, being held in Newcastle UK, June 2016. The collected papers focus on railway research, including topics such as rail operations, engineering, logistics, communication systems and safety. The target audience primarily comprises researchers and experts in the field of railway engineering, but the paper collection may also be beneficial for graduate students alike.